2013
DOI: 10.1177/1555412013478688
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Heteronormativity in Online Games

Abstract: In 2008, ten million people were playing the massive multiplayer role-playing game World of Warcraft (WoW); a fantasy-based virtual landscape where players bridge real-life personas with digital identity. However, the construction of sexuality within this gaming environment has created an oppressive atmosphere for individuals who do not adhere to a heteronormative lifestyle. In this essay, I undress the bottom-up and top-down structures that are regulating an environment that has no use for a constructed sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This paper has looked at some of the ways people constructed support/opposition for the inclusion of a transgender character in World of Warcraft. While previous research has typically shown an antifeminist and anti LGBTQ+ stance on the same fora (see Pulos 2013;Braithwaite 2014), this work has argued that the posters are, on the whole, in favour of including transgender characters. This work has demonstrated the complexities of how transphobic ideologies are expressed through language, and how such ideologies are challenged in an online context.…”
Section: Discussionmentioning
confidence: 56%
“…This paper has looked at some of the ways people constructed support/opposition for the inclusion of a transgender character in World of Warcraft. While previous research has typically shown an antifeminist and anti LGBTQ+ stance on the same fora (see Pulos 2013;Braithwaite 2014), this work has argued that the posters are, on the whole, in favour of including transgender characters. This work has demonstrated the complexities of how transphobic ideologies are expressed through language, and how such ideologies are challenged in an online context.…”
Section: Discussionmentioning
confidence: 56%
“…Research conducted by Amanda Cote (2017), Genesis Downey (2012), and Kishonna Gray (2012) are just a handful of examples detailing the extent to which some women must go to protect themselves from being on the receiving end of hostile behavior while playing MMOG or First-Person Shooter games. Critical discourse analysis of posts to online gaming forums have found that heteronormative undertones of the World of Warcraft player community creates a culture of hostility toward LGBTQ communities (Pulos, 2013) and the same forum's adamant disavowal of feminism have made community conversations about stereotypical gender roles all but non-existent (Braithwaite, 2014). Taken together, this scholarship is evidence that a toxic undercurrent exists across digital cultures, and is not isolated to a particular game or specific player community.…”
Section: Why Do Players Leave Games?mentioning
confidence: 85%
“…A distinctive practice observed in this regard is the utilization of game avatars to participate in virtual sexual and romantic activities (Brown, 2015;Liu, 2019;Sundén & Sveningsson, 2012). Despite the existing scholarship that scrutinizes the cultural significance of transgressive gameplay and its associated ramifications, including homophobia, misogyny, and gender-based harassment (Pulos, 2013;Shaw, 2017;Sundén & Sveningsson, 2012), there is a dearth of research that addresses why the inclusion of queer characters in game design as a strategy for combating homophobia has proven to be unproductive and less appealing to queer players (Pulos, 2013;Shaw, 2017;Sundén & Sveningsson, 2012).…”
Section: Social Games Lgbtq Platforms and Transgressive Gameplaymentioning
confidence: 99%